THE EFFECTIVENESS OF ONLINE MARKETING TRENDS : B2B AND B2C APPLICATION - Ida Ayu Iswari Pidada (Jurnal Ilmiah Manajemen & Bisnis, 2020)
This research aims to determine the effectiveness of online marketing using B2C (Business to Consumer) and B2B (business to business) at Movenpick Resort and Spa Jimbaran, Bali. This research used qualitative methods used in a case study approach. Methods of data collection have used library research with previous research and field research with observation, interviews, and documentation.  The results showed that online marketing using B2B (Business to Business) and B2C (Business to Consumer) was very effective for the sales process at Mövenpick Resort and Spa Jimbaran, Bali it’s seen from the data provided by the sources which showed that the sales period 01 January 2017 - 01 January 2019 the biggest sale is through the internet, that is by using CRS (central reservation system) which is connected from OTA (Online Travel Agent), amounting to 73.2 percent. Whereas sales using the official website from Mövenpick, namely www.movenpick.com or MHR.com are only 6.3 percent. Sales obtained by the front desk/walk-in, telephone and office reservation are only 0.1 percent.